Measurement of Vulnerability of Financial Portfolio of Sharia Commercial Banks by Cardona Method - Paulina Harun; Atman Poerwokoesoemo (Indonesia Banking School, 2017)
his study aims to: (1) to know and analyze the extent of volatility (vulnerability) of sharia banking industry in Indonesia in the face of competition (2) to know and analyze factors affecting vulnerability of sharia commercial banks; (3) to know and analyze the extent of sustainable development of sharia banking industry to Indonesia's economic development.The research conducted to measure the vulnerability (volatility) of proto folio of syariah bank using observation period 2015, and the data used is cross section data. The research design used in this research is quantitative research, using asset dimension (asset portfolio, liability portfolio, equity portfolio) and stressor (pressure, including: credit risk, market risk, and liquidity risk).The activity plan of this research is: in the initial stage of conducting theoretical study related to the vulnerability related to banking especially BUS; The next step is to determine the asset and stressor dimensions associated with the BUS; Further determine the indicators related to assets and stressors; The next step performs calculations to determine the index of each BUS as well as the dimensions that affect the vulnerabilities faced by each BUS.Target expected outcomes can be generated from this research is: for the object of research (BUS) provide a solution for BUS to deal with and overcome the vulnerabilities encountered and policies that must be done. For policy makers, the results of this study are expected to provide input in decision-making and other policies.Measurement of vulnerability to be performed related to banking operations in the face of competition and the continuity of BUS in Indonesia. The outcomes of this study are expected to be included in Bank Indonesia journals, the selection of this journal is based on studies conducted in the banking sector, especially BUS in Indonesia.